PRINSIP SYURAâ DALAM KONSTITUSIONAL ISLAM - Santoso, Lukman (AS-SALAM, 2012)
This topic examines concept âsyuraâ (conference; negoisation) and how toimplement âsyuraâ to the context of constitutional state right now. Includingthe offending with rechstaat/ rule of law. Syura is defined as the mainprinciple for solving the social, politic, and government problems. Syura isthe way to give the opprtunity to the society who has an ablity to participatefor making a decision which binds as well as in the law regulation and politicpolicy. But the implementation of syura althought the institutionalizationof syura, no nash of Al-Qurâan that decribes about it. Prophed MuhammadSAWâthat instituted and cultured syuraâdid not leave the specific patternand the form. Beause of that, the moslems right now and to te next, thepartern and the form of that implementation, are free to initiative. So it canbe appropriated with the condition and the reality. Including that relevancewith the parliamentary democratie concept or the exixtence of legislativeinstiution, especially Indonesia.Keywords: Syuraâ, Konstitusional Islam, Negara Modern